CONSIMŢĂMÂNTUL VICTIMEI – CAUZĂ JUSTIFICATIVĂ SAU CAUZĂ CARE ÎNLĂTURĂ CARACTERUL PENAL AL FAPTEI? - USM ADMIN (Studia Universitatis Moldaviae: Stiinte Sociale, 2010)
Analyzing the law doctrine, we can trace different opinions regarding the matter of the victim's consent in criminal law. Thus, through this investigation we are determined to identify the correct name and exact legal nature of this penal institution. In this regard, in our approach, built on the Russian and Western scientific doctrines; we proposed to confront different visions of the posed problem. Therefore, regarding the victim’s consent as a justification of the offense, we finally reached the conclusion that in criminal law the justification name assigned to the consent of the victim is considered more accurate and in any case, closer to it’s relevant legal content.